PENGARUH EMPLOYEE ENGAGEMENT DAN MODAL SOSIAL TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) KARYAWAN PADA DINAS TANAMAN PANGAN DAN HOLTIKULTURA KABUPATEN ROKAN HULU - Neli Febrida; Purwantoro (Program Studi Manajemen Universitas Pasir Pengaraian, 2020)
This study aims to determine how the effect of employee engagement and social capital on organizational citizenship behavior (OCB) of the Food Crop and Horticultural Employees of Rokan Hulu Regency, both partially and simultaneously. Data collection methods in this study through observation, questionnaires and literature studies. The sample in this study were 65 employees of the Food Crops and Horticulture Office in Rokan Hulu Regency. The sampling technique used was accidental sampling. Data analysis techniques using multiple linear regression, hypothesis testing consisting of the F test, t test and the coefficient of determination. From the results of t-test test shows that employee engagement variable has a positive and significant effect on organizational citizenship behavior (OCB) with a significance value <0.05 ie 0,000, social capital has a positive and significant effect on organizational citizenship behavior (OCB) with a significance value <0, 05 which is 0,000. Through the F test employee engagement variables and social capital together have a significant effect on organizational citizenship behavior (OCB) with a significance level of 0,000. In the determination coefficient test it is known that 97.6% organizational citizenship behavior (OCB) is influenced by employee engagement and social capital, while the remaining 2.4% is explained by other variables not examined in this study or other causes beyond model.